Analisis Infrastruktur Jaringan Wireless antar Pulau Studi Kasus Pulau Marore - Tahuna (Lenganeng) - Ella H. Israel; Alfrianus Papuas (Jurnal Ilmiah Tindalung, 2015)
Sangihe Islands District is an area of the country bordering Indonesia Philippines, as the border area is certainly very susceptible to interference from outside, either from the field defends and security to the socio-economic field it is due to the limitations of the communication between the outer islands of the surrounding islands, the existing information can not be conveyed properly and quickly, for it required an information technology that can reach up to the stricken islands. This study aims to provide the best solutions on what the appropriate infrastructure for inter-island archipelago Sangihe district, especially between Marore with Sangihe Island. (Outermost island of Indonesia, which is directly adjacent to the neighboring countries of the Philippines). The method used in this study using a prototype method, with this method we can more quickly get a picture faster of needs, but it also can detect errors early.